2021
DOI: 10.3389/fpls.2021.769151
|View full text |Cite
|
Sign up to set email alerts
|

Reversed-Phase HPLC Characterization and Quantification and Antioxidant Capacity of the Phenolic Acids and Flavonoids Extracted From Eight Varieties of Sorghum Grown in Austria

Abstract: Sorghum is raising great interest as a grain for the future, for its agricultural advantages in times of climate change, and for the positive impact of its bioactive compounds on human health. These compounds comprise phenolic acids, in a free, conjugated, and bound form, and flavonoids. The most commonly used extraction methods require high volumes of chemicals and are non-practical when handling many samples at a time. The main aim of this study was to develop a microscale extraction procedure for both pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 45 publications
(68 reference statements)
1
7
0
Order By: Relevance
“…and Kupe et al ., 56,57 have also found a significant correlation between total phenol content and antioxidant activity. A statistically significant correlation between FRAP and free phenolic acids has also been reported by Speranza et al 58 . in sorghum kernels.…”
Section: Discussionsupporting
confidence: 78%
“…and Kupe et al ., 56,57 have also found a significant correlation between total phenol content and antioxidant activity. A statistically significant correlation between FRAP and free phenolic acids has also been reported by Speranza et al 58 . in sorghum kernels.…”
Section: Discussionsupporting
confidence: 78%
“…Xu et al [ 30 ] reported that polyphenols can negatively affect wheat bread volumes. According to Speranza et al [ 31 ], red sorghum varieties contained more polyphenols than white sorghum varieties, which may have contributed to the smaller volume of red sorghum breads. Overall, the pseudocereals influenced SBW volume the most, most likely caused by their different protein composition.…”
Section: Resultsmentioning
confidence: 99%
“…In a few reported methods of these phytochemicals (chlorogenic acid, catechin, and epicatechin), they were separated up to 40 to 60 min. [11,12] The important aspect of the new HPLC method developed in the current study was the less time used for the separation for phytochemicals (< 20 min).…”
Section: Hplc-dad Analysismentioning
confidence: 99%